Should the Maharajah be Dethroned ? A Case Study of Air India - Costa, Juao (Prabandhan: Indian Journal of Management, 2021)
Air India, like any other public sector undertaking/government company, is incurring losses and trapped under the heavy burden of debt. The taxpayers’ money is being utilized to keep the sinking Maharajah on a ventilator. The first attempt to sell 76% stake in Air India failed miserably due to several reasons as identified by the transaction advisor of the Government of India. The reasons are Government of India’s 24% ownership and equivalent rights, heavy debt around INR 38,000 crores, fluctuations in macro environment, no individual bidding, consistent losses, and buyers not being able to form a cartel within the given time period. Why is that such a big ship is drowning today ? Is it overburdened with the losses and loans? Why is it unable to introduce some revival strategy ? What are the reasons responsible for its failure? Disinvestment should be the last option, especially for a rich entity and a national carrier like Air India. However, the government is in a hurry to exercise its last option, which is to sell it. The government has now made a second attempt to modify and sell it under promising conditions. The main objective of this case study was to discuss the current situation of Air India and examine the best option available for it, including reverting the decision to sell. The case provided pointers concerning all the options available for the airline.